2015
DOI: 10.1002/jps.24596
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profiles of Active Components After Oral Administration of a Kampo Medicine, Shakuyakukanzoto, to Healthy Adult Japanese Volunteers

Abstract: Shakuyakukanzoto (SKT), a traditional Japanese (Kampo) medicine, has been used by patients with muscle cramps and abdominal pains. In this trial, we analyzed plasma concentrations of active components after SKT was administered as a single oral dose of 2.5 or 5.0 g/day per person. The study was a randomized, open-label, two-arm, two-period, crossover trial conducted in healthy Japanese volunteers. Albiflorin (ALB), paeoniflorin (PAE), glycycoumarin (GCM), isoliquiritigenin (ILG), glycyrrhetic acid (GA), and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…However, such a bimodal pattern has not been observed in the plasma when EPD is orally administered to rats15. Although the reason was unclear in this study, the bimodal distribution has been reported to be caused by several factors, such as the coexistence of the precursor16, enterohepatic circulation17, and plural absorption regions (small and large intestines)18 for the ingredients in the Kampo medicine. Why the second peaks of the lung concentrations of both ingredients were delayed with an increasing the dosage of maoto remains unclear.…”
Section: Discussionmentioning
confidence: 74%
“…However, such a bimodal pattern has not been observed in the plasma when EPD is orally administered to rats15. Although the reason was unclear in this study, the bimodal distribution has been reported to be caused by several factors, such as the coexistence of the precursor16, enterohepatic circulation17, and plural absorption regions (small and large intestines)18 for the ingredients in the Kampo medicine. Why the second peaks of the lung concentrations of both ingredients were delayed with an increasing the dosage of maoto remains unclear.…”
Section: Discussionmentioning
confidence: 74%
“…The major compounds of HNS (platycodin D, paeoniflorin, and hesperidin) have been shown to be able to be delivered into blood . We suggest, however, that the effects of HNS are expected not only in the blood circulation but also directly in the oral cavity, because high‐concentration intraoral HNS can directly affect periodontal disease‐related bacteria in the oral cavity.…”
Section: Discussionmentioning
confidence: 89%
“…The blood levels of selected terpenes after administration of a single dose and their effective concentrations which exert biological effects are presented in Table 2 [77][78][79][80][81][82][83][84][85][86]. In most cases a higher single dose is required to reach the effective terpene concentration in the serum; however, the half time of these compounds' elimination from the blood is rather long, and repeated doses or a daily diet containing these compounds may be sufficient to maintain a safe, but stable, effective concentration.…”
Section: Discussionmentioning
confidence: 99%